2020
DOI: 10.1016/j.heliyon.2020.e04830
|View full text |Cite
|
Sign up to set email alerts
|

Integration of medicinal plants into the traditional system of medicine for the treatment of cancer in Sokoto State, Nigeria

Abstract: This study was designed to explore and record various medicinal plants integrated into the traditional system of medicine for the treatment of cancer. The traditional system of medicine is a routine practiced among the indigenous ethnic groups of Sokoto state. A semi-structured questionnaire was designed and used for data collection around the selected Local Government Areas. A substantial number of plant species were identified, recorded, and collected for preservation. Data collected for each specie was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 185 publications
(125 reference statements)
1
12
0
Order By: Relevance
“…Fruit and ower were the least used parts in two and one preparation with 5.0% and 2.5% respectively (Figure 4.1). The results are in line with the ndings of several documented studies carried out in different localities of Northwestern Nigeria, which showed stembark and leaves as frequently used plant part [19], [7], [2], [22] . The reason behind the extensive use of stem back would be obvious when one considers that this region is arid in nature, with very low amount of rainfall and hence there would be great conservation and retention of secondary metabolites present in the stem back due to constant metabolic activity triggered by harsh environmental conditions.…”
Section: Parts Usedsupporting
confidence: 89%
See 1 more Smart Citation
“…Fruit and ower were the least used parts in two and one preparation with 5.0% and 2.5% respectively (Figure 4.1). The results are in line with the ndings of several documented studies carried out in different localities of Northwestern Nigeria, which showed stembark and leaves as frequently used plant part [19], [7], [2], [22] . The reason behind the extensive use of stem back would be obvious when one considers that this region is arid in nature, with very low amount of rainfall and hence there would be great conservation and retention of secondary metabolites present in the stem back due to constant metabolic activity triggered by harsh environmental conditions.…”
Section: Parts Usedsupporting
confidence: 89%
“…These results are relatively in line with those of previous ethnobotanical studies conducted for within the extreme Northwest region of the country, which has basically a Sahel vegetation. The frequent use of medicines from trees and shrubs plant species here, could be attributed to the desertic nature of the place, which does not accommodate a rich biodiversity of other plants life form that cannot withstand drought and other arid weather conditions, among other reasons [19], [7], [2], [20].…”
Section: Life Formmentioning
confidence: 99%
“…Furthermore, it serves as a promising source of phytochemical compounds used for the development of conventional medications (Yuan et al 2016). In Africa and other developing countries, most people rely on herbal medications for primary healthcare (Malami et al 2020). Guiera senegalensis (Combretaceae) is a medicinal plant that is widely distributed in the savannah regions of west and central African countries, such as Nigeria, Senegal, Gambia, Mali, Niger, Burkina Faso and Ghana (Salihu & Usman 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reason is attributed to the observed positive effects of alternative medicines in overall human health care ( Tesfahuneygn & Gebreegziabher, 2019). Alternative medicine has proved to be an effective health care solution for many people in all cultures (Malami et al, 2020). Accordingly, there has been an increased dependence on alternative medicine for primary health care sources (Prinsloo et al, 2018).…”
mentioning
confidence: 99%
“…Over the years, medicinal plants have been widely used in Nigeria as an alternative therapeutic provision. Insinuations suggest that the country is naturally endowed with plant biodiversity, generally employed in health care (Malami et al, 2020). Accordingly, Chukwuma et al (2015) contend that medicinal plants have assumed a vital role in the Nigerian healthcare sector.…”
mentioning
confidence: 99%